Trends in serum relaxin concentration among elite collegiate female athletes - Jason L Dragoo; Tiffany N Castillo; Tatiana A Korotkova; et al (Dove Medical Press, 2011)
Jason L Dragoo1, Tiffany N Castillo1, Tatiana A Korotkova1, Ashleigh C Kennedy1, Hyeon Joo Kim1, Dennis R Stewart21Department of Orthopaedic Surgery, Stanford University, Palo Alto, CA, USA; 2Corthera Inc. San Mateo, CA, USAPurpose: This study was designed to investigate the relationship between serum relaxin concentration (SRC) and menstrual history and hormonal contraceptive use among elite collegiate female athletes. Evaluation of SRC in athletes is necessary, because relaxin has been associated with increased knee joint laxity and decreased anterior cruciate ligament (ACL) strength in animal models.Methods: National Collegiate Athletic Association Division I female athletes participating in sports at high risk for ACL tears – basketball, field hockey, gymnastics, lacrosse, soccer, and volleyball – were invited to participate. All participants completed a questionnaire about their menstrual history and hormonal contraceptive use. Venipuncture was performed to obtain samples of serum progesterone and relaxin. Samples were obtained during the mid-luteal phase from ovulating participants, and between the actual or projected cycle days 21 to 24, from anovulatory participants. Serum concentration of relaxin and progesterone was determined by ELISA and the data were analyzed using SPSS statistical software with significance set at P = 0.05.Results: 169 female athletes participated. The mean SRC among all participants was 3.08 ± 6.66 pg/mL). The mean SRC differed significantly between those participants using hormonal contraceptives (1.41 pg/mL) and those not using hormonal contraceptives (3.08 pg/mL, P = 0.002). Mean SRC was lowest among amenorrheic participants (1.02 pg/mL) and highest among oligomenorrheic participants (3.71 pg/mL) and eumenorrheic participants (3.06 pg/mL); these differences were not significant (P = 0.53). Mean serum progesterone concentration (SPC) differed significantly between those participants using hormonal contraceptives (2.80 ng/mL), and those not using hormonal contraceptives (6.99 ng/mL, P < 0.0001).Conclusions: There is a positive correlation between serum progesterone and SRC and an attenuation of SRC with hormonal contraceptive use. Our results underscore the significant role that hormonal contraceptives can play in decreasing relaxin levels, if future investigations establish a link between relaxin levels and ligamentous injury among female athletes.Keywords: hormones, ACL, anterior cruciate ligament, hormonal contraceptives, menstrual cycle